Carcinomas of the Uterine Cervix: Comprehensive Review With An Update on Pathogenesis, Nomenclature of Precursor and Invasive Lesions, and Differential Diagnostic Considerations. (18th May 2021) - Arafah, Maria; Rashid, Sameera; Tulbah, Asma; Akhtar, Mohammed
Abstract : Most cervical carcinomas and their related lesions are attributed to an infection by human papillomavirus (HPV). The infection usually starts in the basal cells at the squamocolumnar junction. It causes cell proliferation and maturation abnormalities along with nuclear abnormalities resulting in low-grade squamous intraepithelial lesions. An overwhelming majority of these lesions spontaneously disappear, and the infection is cleared. In a small subset of high-risk HPV infection cases, the lesions may persist and progress to high-grade squamous intraepithelial lesions. These are associated with the incorporation of the viral genome into the human genome. Some of the high-grade squamous intraepithelial lesions, over several years, progress to invasive carcinoma. Carcinomas of the cervix are usually squamous cell carcinomas (SCCs), but 20% to 25% of the cases may manifest as adenocarcinomas. Similar to SCC, adenocarcinomas may initially manifest as adenocarcinomas in situ and may progress to invasive carcinomas after a variable period of time. In the recently published World Health Organization classification of female genital tumors, SCCs, and adenocarcinomas of the cervix are divided into HPV-associated and HPV-independent tumors. This review draws on the latest terminology and the several morphologic subtypes recognized for each category.